Interleukin-38 and Insulin Resistance - Klejbuk, Kamil; Strączkowski, Marek (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Insulin resistance, i.e., decreased biological response to insulin, is a risk factor for many diseases, such as obesity, type 2 diabetes (T2DM), cardiovascular disease, polycystic ovary syndrome, some forms of cancer and neurodegenerative diseases. One of its main causes is chronic low-grade inflammation, mediated by the proinflammatory pathways, such as the c-Jun N-terminal kinase (JNK) pathway and the nuclear factor kappa B (NFΚB) pathway. Interleukin (IL)-38 (IL-38) is a newly discovered cytokine that belongs to the IL-1 family. There are three hypothetical pathways through which IL-38 may bind to the specific receptors and inhibit their proinflammatory activity. Those pathways are associated with IL-36 receptor (IL-36R), IL-1 receptor accessory protein-like 1 (IL1RAPL1) and IL-1 receptor 1 (IL1R1). There are studies linking IL-38 to improve insulin sensitivity through the difference in serum IL-38 in patients with insulin resistance or the correlation of IL-38 concentrations with insulin resistance indexes. However, many questions still remain regarding the biological activity of IL-38 itself and its role in the pathogenesis of insulin resistance. The goal of this study is to showcase IL-38, its biological activity, hypothesized signaling pathways, connection with insulin resistance and future perspectives of research on IL-38. We present that IL-38 associated signaling can be a potential target for the treatment of insulin resistance and associated diseases.
Keywords: insulin sensitivity